Effectiveness of ICT Based Learning Material in Science Learning
In the present study researchers developed an /CT based learning material. It was a self/ earning material, which was based on the principles of programmed learning. In the present study, an /CT based programmed learning material was developed on the topics "Matter in our surroundings" and "Is matter around us pure" based on the content of the NCERT Science textbook for class IX Students. The sample for the present study comprised of 180 students of class IX. A quasi-experimental research design was adopted for the study. This study involved the dependent variable as -Treatment Groups (Experimental Group Vs. Control Group